Comunicação, recepção e consumo: suas inter-relações em rebelde-RBD - Budag, Fernanda Elouise
The study object of this dissertation are the intersections reception/consumption in the Rebelde soap opera and RBD teenage band, searching the influence of that product of media culture (Rebelde-RBD) in the formation process of teenagers identities. The emphasis is in the questions related to the production of meanings, appropriations and reappropriations, and also the construction of social representations that happen in the reception process and interfere on the constitution of these teenagers as individuals. We approach the consumption practices that involve the interaction between the material and symbolical spheres, emphasizing the singularities that Rebelde-RBD promotes in these practices: we notice an extension, a kind of privilege of the symbolical pole related to the material one. The research sought to identify which values the young public imputes to the material consumption linked to the symbolical consumption and, mainly, what are the points that the teenagers emphasize as the motivations to the imperative that, in the specific case of this media product, we notice to exist in what concerns to the acquisition of the objects relative to the soap opera and the band and what is the concrete result of this reception/consumption movement in the formation of individual identities